Enhancing labor outcomes through non-pharmacologic interventions: a study on birthing ball and deep breathing relaxation in Indonesia - Fitriana, Fitriana (Jurnal Kesehatan Ibu dan Anak, 2025)
Labor during the active phase of the first stage is often associated with significant pain and anxiety, which can prolong labor and negatively impact outcomes. Non-pharmacologic interventions such as birthing ball (BB) and deep breathing relaxation (DBR) have been introduced to address these challenges. However, comparative studies evaluating their effectiveness are limited. This study compares the effects of DBR and BB exercise on mothers' anxiety, pain threshold, and progress during the active phase of labor. This quasi-experimental study comprised 46 participants who were consecutive sampling to one of two groups using sequential sampling: DBR (n = 23) or BB (n = 23). The study had a pretest-posttest two-group comparison design.  Interventions were carried out by midwifery led care in Pringsewu, Indonesia, from November 2024 to April 2025, during the active phase of labor.  Data were collected using the State-Trait Anxiety Inventory (S-TAI) scale, partograph, Visual Analog Scale (VAS), and Labor and Delivery Satisfaction Questionnaire (LDSQ) mother satisfaction survey.  The statistical analysis employed paired t-tests and Mann Whitney. Labor pain was considerably decreased by both therapies (DBR: mean reduction from 4.3 to 3.6; BB: mean reduction 4.5 to 3.8; p < 0.01).  Following the therapies, anxiety levels also dropped, though not statistically significantly in DBR group 52.2 to 49.4; p < 0.05 and BB group 50.4 to 48.3; p< 0.00.  In comparison to the DBR group (mean = 274.3 ± 29.3 minutes; p = 0.003), the BB group's active phase duration was significantly shorter (mean = 243.5 ± 31.1 minutes).  In comparison to the DBR group (mean = 31.3 ± 3.1; p < 0.001), maternal satisfaction was significantly higher in the BB group (mean = 34.2 ± 3.7). Both DBR techniques and BB activities can help reduce pain and accelerate the labor process.  However, BB exercises were more effective in shortening the duration of labor and increasing mother satisfaction.  These findings support the use of non-pharmacological treatments in routine intrapartum care, especially in under resourced areas. These findings suggest that midwives and healthcare providers should consider incorporating BB exercises into standard intrapartum care protocols, especially in resource-limited settings.